2000
DOI: 10.1139/bcb-78-2-99
|View full text |Cite
|
Sign up to set email alerts
|

Novel α4-integrin ligands on an endothelial cell line

Abstract: The unique combination of adhesion molecules expressed on endothelial cells is thought to mediate the specificity of leukocyte-endothelial cell interactions. In this study, murine endothelial cell lines were used as a model to identify novel adhesion molecules that participate in these cellular interactions. Lymphocyte adhesion to the continuous endothelial cell lines mHEVa and mHEVc required alpha 4-integrin. Interestingly, lymphocyte alpha 4-integrin bound to VCAM-1 as well as an unknown ligand on the mHEVa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…We have reported that lymphocytes bind and migrate across monolayers of the endothelial cell lines, mHEVa and mHEVc (11). We have also previously determined by Ab inhibition studies that adhesion of resting lymphocytes to these endothelial cell lines is dependent on lymphocyte ␣ 4 integrin binding to VCAM-1 on the mHEV cells (12). Therefore, we determined whether adhesion via ␣ 4 integrin to VCAM-1 was required for lymphocyte migration.…”
Section: Lymphocyte Adhesion Is Required For Lymphocyte Migration Acrmentioning
confidence: 89%
See 1 more Smart Citation
“…We have reported that lymphocytes bind and migrate across monolayers of the endothelial cell lines, mHEVa and mHEVc (11). We have also previously determined by Ab inhibition studies that adhesion of resting lymphocytes to these endothelial cell lines is dependent on lymphocyte ␣ 4 integrin binding to VCAM-1 on the mHEV cells (12). Therefore, we determined whether adhesion via ␣ 4 integrin to VCAM-1 was required for lymphocyte migration.…”
Section: Lymphocyte Adhesion Is Required For Lymphocyte Migration Acrmentioning
confidence: 89%
“…During lymphocyte migration across the mHEV cell lines, the endothelial cells change shape by retracting their membrane at the site of the lymphocyte, the lymphocyte migrates between adjacent endothelial cells within a few minutes, and the endothelial cells reform their cell-cell junction (11). The mechanism for lymphocyte adhesion to the mHEV cell lines is by lymphocyte ␣ 4 integrin binding to VCAM-1 on the mHEV cells and not to any other known adhesion molecule (12). The expression of VCAM-1 by the mHEV cell lines is constitutive (11), in contrast to other endothelial cells that require cytokine activation of VCAM-1 expression.…”
mentioning
confidence: 99%
“…B6RV2 cells were maintained in RPMI with 15% FBS. Murine ECs, mHEVc, were cultured as described (Cook-Mills et al 1996;Tudor et al 2000).…”
Section: Cell Lines and Growth Conditionsmentioning
confidence: 99%
“…Therefore, spleen cells (3 ϫ 10 6 ) were added to the flow chamber (3.5 cm 2 ) at 2 dynes/cm 2 . Spleen cells were added at concentrations below saturation of monolayer cell binding or migration (12,24). To initiate spleen cell contact with the endothelial cells in vitro, the spleen cells were allowed to settle in the chamber as monitored by microscopy and then 2 dynes/cm 2 was applied for the 15 min laminar flow assay.…”
Section: Cell Association and Migration Assays With Laminar Flowmentioning
confidence: 99%
“…The endothelial cell lines, mHEVa and mHEVc, constitutively express VCAM-1 and do not express other ligands for lymphocyte migration such as ICAM-1, PECAM-1, and E-selectin as determined by immunofluorescence labeling (24) or cDNA microarray analysis (data not shown). Furthermore, adhesion and migration across the endothelial cells are dependent on binding to VCAM-1 and the constitutive expression of MCP-1 by the endothelial cells (9,24,25). Abs for other adhesion molecules other than VCAM-1 or its ligand ␣ 4 ␤ 1 integrin do not block lymphocyte migration across the endothelial cells (12).…”
mentioning
confidence: 98%